The other side of empathy - Davis, Jade E. (Duke University Press, 2023)
"The Other Side of Empathy argues that empathy itself is a culturally created and maintained affective ideology deployed to make sense of a world that has been irrevocably distorted by colonization and technology. Understanding empathy culture, and empathy as an ideology allows for an exploration of its arbitrariness, cultural contradictions, and limits. An analysis of "human zoos," as presented in colonial photography and in their digital afterlife, illustrates how ingrained proper empathetic responses are built into culture. Emerging technologies, such as Artificial Intelligence and Virtual Reality, ensure that colonial dynamics are maintained into the future despite information that allows other ways of understanding the past. The Other Side of Empathy attempts to illustrate how we can dismantle empathy to allow for more nuanced and complete understandings of the colonial past and its impact on the world today"--